Olive trees as bio‐indicators of climate evolution in the Mediterranean Basin. Issue 7 (17th April 2013) - Moriondo, Marco; Trombi, Giacomo; Ferrise, Roberto; Brandani, Giada; Dibari, Camilla; Ammann, Caspar M.; Lippi, Marta Mariotti; Bindi, Marco
Abstract Aim This paper aims to project areas of olive cultivation into future scenarios. Accordingly, we first asked the question whether global circulation models (GCMs) are able to reproduce past climatic conditions and we used historical ranges of olive cultivation as a palaeoclimate proxy. Location The Mediterranean basin. Methods We used an ecological model, calibrated and validated for modern times, to test the reliability of a general circulation model (NCAR‐CSM GCM) in reproducing past ranges of olive tree cultivation inferred from the literature, archaeo‐botanical investigations and fossil pollen analyses. Results The re‐constructions of olive growing areas, obtained for the Medieval Climate Anomaly (MCA, 1200‐1300 AD) and the Little Ice Age (LIA, 1600‐1700 AD) by coupling the outputs of NCAR‐CSM to the ecological model, were in agreement to those observed. Simulations of olive growing areas for future time‐windows showed that a northwards expansion of the species is expected to occur by 2100. Main conclusions These results demonstrate that the NCAR‐CSM can provide an accurate reconstruction of past climate with results sensitive to climate forcing factors and thus, it is more likely to give reliable projections for the future. Additionally, the warming and drying conditions expected in the coming decades may determine changes across the Mediterranean basin that is unprecedented.